The Jewish Press and the Holocaust, 1939-1945 : Palestine, Britain, the United States, and the Soviet Union. - Gorny, Yosef (Cambridge books online., 2011)
This book shows the reaction of the Jewish press in the free countries in the face of the Holocaust.